2020
DOI: 10.1111/jpc.15179
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric periorbital cellulitis: A 10‐year retrospective case series review

Abstract: Aim To identify the predictors of poor outcome and need for surgical management in paediatric patients with periorbital cellulitis. To assess the adherence to local guidelines in the management of periorbital cellulitis. Methods Retrospective descriptive analysis of clinical, laboratory and radiological characteristics of 175 paediatric periorbital cellulitis presentations at a UK teaching hospital over a 10‐year period. Regression investigated correlations for continuous and categorical variables. Results A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…This management is supported in the literature, which suggests that multidisciplinary management and early intervention can improve outcomes for children with periorbital cellulitis. 23 Canadian data have also demonstrated over-representation of facial cellulitis among paediatric inpatients (26.8%) compared with non-admitted patients (16.3%) with cellulitis. 24 Similarly, Canadian ED presentations were also predominantly extremity cellulitis (69.5%), due to insect bite (21.6%) and trauma (20.3%).…”
Section: Discussionmentioning
confidence: 96%
“…This management is supported in the literature, which suggests that multidisciplinary management and early intervention can improve outcomes for children with periorbital cellulitis. 23 Canadian data have also demonstrated over-representation of facial cellulitis among paediatric inpatients (26.8%) compared with non-admitted patients (16.3%) with cellulitis. 24 Similarly, Canadian ED presentations were also predominantly extremity cellulitis (69.5%), due to insect bite (21.6%) and trauma (20.3%).…”
Section: Discussionmentioning
confidence: 96%
“…The orbital surgery rate in the current study was 28.5% in the OC group and 2.6% overall. In a study which evaluated 175 pediatric cases (36 had OC), 27 patients had subperiosteal abscess and surgery was needed in 31 (1.7%) of all patients [10]. Another study found the rates of surgical intervention as follows: 29% overall (n = 93), 48.7% in the 39 patients with OC and 14.8% in the 54 patients with PC.…”
Section: Discussionmentioning
confidence: 99%
“…OC), and all patients with OC had sinusitis as a predisposing factor [9]. A recently published study reported that 68% of pediatric PC and OC cases had respiratory tract infection or sinusitis [10]. In a retrospective cross-sectional study from a tertiary ophthalmology hospital including 93 pediatric and adult patients (39 OC and 54 PC), it was reported that sinusitis was the most common etiology in both groups and was signi cantly more frequent in the OC group [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Periorbital cellulitis is categorized as either preseptal or orbital cellulitis, which are defined as infections of the subcutaneous tissue anterior to the orbital septum and soft tissue posterior to the septum, respectively [ 1 , 2 , 3 ]. Recent studies on periorbital cellulitis in children have focused mainly on patient characteristics, clinical presentations, laboratory findings, and treatment effectiveness [ 1 , 2 , 3 , 4 , 5 , 6 ]. For example, a higher incidence of orbital cellulitis in males over females has been reported [ 7 ], and pediatric preseptal cellulitis is more common in younger patients than orbital cellulitis [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%